Seventeenth-century chant manuscripts held at University of Warsaw Library in the context of Bernardine musical culture - Grabiec, Dominika (Interdisciplinary Studies in Musicology, 2018)
The Music Department at Warsaw University Library is in possession of three seventeenthcentury chant manuscripts. All three were probably produced in the Bernardine community, although only two of them contain provenance notes which allow us to establish more precisely where they were compiled or used. In the present paper, the focus is on one of those manuscripts, which formerly belonged to the Bernardine nuns of Łowicz. This source provides valuable information on such subjects as the exchange of musical experiences and cooperation among various congregations.